Cephalometric evaluation of Brahmins of Kathmandu, Nepal based on Jarabak’s analysis - Pokharel, Mona; Shrestha, Situ Lal (Journal of Kathmandu Medical College, 2019)
Background: The cephalometric norms derived from Caucasian population shows a great degree of variation when applied to different population. Objectives: The present research was performed with the objective of determining cephalometric norms of Brahmins of Nepal based on Jarabak’s analysis, to evaluate the variability between male and female and to compare the cephalometric norms with Caucasians. Methodology: Lateral cephalogram of 108 non-growing patients which consisted of 63 females and 45 males of Nepalese Brahmins who met our inclusion criteria were traced manually. Thirteen craniofacial parameters of Jarabak’s analysis were measured. Results: The comparison between Brahmin populations of Nepal with the Caucasian population showed statistically significant difference in ten out of thirteen parameters. The comparison between Nepalese male Brahmins and female Brahmins showed that there were statistically significant differences in eleven out of thirteen parameters. Conclusion: It can be concluded that there exists sexual and ethnic dimorphism in craniofacial features. The findings of the study highlight the fact that Brahmin population is significantly different from Caucasian population. Females presented with smaller craniofacial variable than male when gender comparison was performed among Nepalese Brahmins male and female. This research has helped to generate knowledge and understanding of craniofacial features of Nepalese Brahmins and derived norms for orthodontic diagnosis and treatment planning.